A Multisite Examination of Everyday Discrimination and the Prevalence of Spontaneous Preterm Birth in African American and Latina Women in the United States - Fryer, Kimberly E.; Vines, Anissa I.; Stuebe, Alison M. (American Journal of Perinatology, 2019)
Objective African American women have a higher risk of spontaneous preterm birth than White and Latina women. Although Latina women are exposed to similar social determinants of health, they have lower rates of spontaneous preterm birth. One theory for this difference is the maternal stress biological pathway, whereby lifetime stressors, such as racial discrimination, lead to a premature activation of parturition. We investigated the prevalence of self-reported discrimination and its association with the prevalence of spontaneous preterm birth.Study Design Using data from the Community Child Health Research Network Study, a multisite cohort study from 2008 to 2012, we conducted a cross-sectional analysis of 1,154 African American women and 578 Latina women.Results Adjusting for multiple risk factors, African American and Latina women who experienced the highest tertile of discrimination had a higher prevalence of preterm birth compared with those who experienced discrimination less than once per year, adjusted hazard ratio (aHR) = 1.5 (0.7–3.1) and 3.6 (0.9–14.4), respectively.Conclusion In our cohort, we found a statistically significant association only in the medium discrimination group in Latina women, but we did not find a statistically significant association in African American women. Reduction in experienced discrimination may be an important intervention for reducing adverse pregnancy outcomes.
Keywords: discrimination; preterm delivery; preterm birth; race; ethnicity; Latina; African American; Hispanic